Optimization Design of Transmission Ratio for Lattice Cage Dust Filter based on Mathcad Analysis - Cao Wei; Liu Dulong; Zha Wenwei; Chen Xianzong (Jixie chuandong)
The coincidence point distribution under transmission for different numbers of teeth on a lattice cage dust filter in the suction arm is analyzed by using Mathcad. From function image of 180°sin x and 180°sin（ 0. 75x） in the interval- 30 and 30,existing designs of gear ratio is found irrational,and then look for a high overlap matching gear. For providing the theoretical basis to improve the efficiency of cross- rotation mechanism suction arm rotation transmission,thereby the gear transmission ratio is optimized. Then,the amount of processing dust filter and the effects of dust are increased,and energy consumption is reduced,while saving operating costs.